If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = -2(x + -7) + -5x Reorder the terms: 7 = -2(-7 + x) + -5x 7 = (-7 * -2 + x * -2) + -5x 7 = (14 + -2x) + -5x Combine like terms: -2x + -5x = -7x 7 = 14 + -7x Solving 7 = 14 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 7 + 7x = 14 + -7x + 7x Combine like terms: -7x + 7x = 0 7 + 7x = 14 + 0 7 + 7x = 14 Add '-7' to each side of the equation. 7 + -7 + 7x = 14 + -7 Combine like terms: 7 + -7 = 0 0 + 7x = 14 + -7 7x = 14 + -7 Combine like terms: 14 + -7 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| log(8)16=x-1 | | 8(2x+1)+5=-3 | | (8+16)-g=4 | | 13x=4/5 | | 36/72=4/z | | -7x+3=4x-3 | | m+10g=239.50 | | 4(2x-3)=-52 | | -5(3m^3+7n^2)+8n^2= | | 16/80=2/t | | 4(2x-3)=-53 | | 9-2x=7x+9 | | 24/18=r/3 | | 9x+1=15-5x | | 5y-26=29 | | 6-3x=7x-24 | | -17+X=-4(-10x+3)-5 | | 5x+1=4+2x | | 3/5=r/40 | | y-8=-2(x+2) | | -45-4x=-7(5x-3)-4 | | 24/40=3/r | | 4(3x-1)=x+7 | | 7+3x=15-5x | | 6x+5=2x-19 | | -8x/-8-7 | | 12+5x=3-4x | | M=x-10x | | 18/12=6/n | | 24.5=-8+9.5(h-3.5) | | 4+9=12 | | 2w+2l=48 |